Challenge of bacteriophage application to improve food safety and its administration into the human gut: an article review - Qori Emilia (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2020)
Ensuring microbial food safety has always been a challenge at every stages along the food chain. Meanwhile, healthier community lifestyle demands natural antimicrobial agents to alleviate the increasing use of chemical preservatives to address microbial contamination. Antimicrobial resistance issue has also elevated the effort to search for an alternative way to antibiotics. Bacteriophage (phage) is currently being assessed for its potency as a biocontrol agent to enhance food safety and as a tool for therapeutic purposes. Prior to phage application, safety assessment must be conducted in which includes several considerations: from the discovery, toxicological aspects to the impact of phage ingestion on the gut microbiota. The gut microbiota which consist of variety of microorganisms inside the human gastrointestinal tract, cohabitate to each other. Phage is naturally present as one of microorganisms in the human gut and dynamically interacted with other microbial communities. Phage application to foods and food-contact surfaces may leave a residue and cause the phages to be ingested, which in result may alter the gut microbiota composition. Many findings have examined the relationship between gut microbiota and human health, and so is the factors affecting their modulation. This review aimed to discuss several points of view from published research papers related to the challenge of phage to improve food safety and its administration into the human gut.